Heterogeneous influences of urban compactness on air pollution: evidence from 285 prefecture-level cities in China - Dan Yan; Shaoxuan Huang; Guoliang Chen; Huan Tong; Peiyuan Qin (Humanities & Social Sciences Communications)
Abstract Fine particulate matter (PM2.5) pollution can harm the climate, the environment, and human health. With sustainability initiatives receiving increasing attention, whether compact urban development can yield green environmental benefits has become an essential research proposition among urban planners. The compact city theory advocates energy efficiency enhancement through the mutual superposition of urban functions. First, a theoretical analysis framework for the effect of urban compactness on environmental quality was constructed. Second, on the basis of panel data from 285 prefecture-level cities in China from 2010 to 2021, exploratory spatial data analysis (ESDA) was applied to reveal the spatiotemporal nonstationary distribution of urban PM2.5 pollution. Finally, the heterogeneous influence mechanisms of compact urban factors on PM2.5 pollution were empirically studied through the geographical and temporal weighted regression (GTWR) model. The main findings are as follows: (1) From 2010 to 2021, the proportion of cities in China with good air quality significantly increased. The cities with high–high pollution clustering are currently located mainly in Beijing–Tianjin–Hebei, Shandong, and Henan. (2) Economic and transportation compactness factors mitigated PM2.5 pollution in most cities, whereas the long-term combined effects of the population and land compactness factors may have exacerbated urban PM2.5 pollution. (3) There was significant spatial and temporal heterogeneity in the effects of urban compactness factors on air pollution. Cities where land-use compactness exerts a pollution mitigation effect were located east of the Hu line. Cities in Northeastern China had the strongest pollution mitigation effect from transportation compactness, followed by the cities in Southwestern China.